Anthropogenic Scarring of Western Gray Whales ( Eschrichtius robustus ) - Bradford, Amanda; Weller, David; Ivaschenko, Yulia; Burdin, Alexander; Brownell, Robert L., Jr. (DigitalCommons@University of Nebraska - Lincoln, 2009)
Western gray whales (Eschrichtius robustus) are critically endangered and anthropogenic threats, such as entanglement in fishing gear and collisions with vessels, may be acting to limit recovery of the population. Thus, examining the magnitude of such anthropogenic interactions using a scar-based approach is warranted. A multi-year (1995–2005) photo-identification study of western gray whales on their feeding ground off northeastern Sakhalin Island, Russia, has resulted in a large data set of digital and film images of 150 individuals. These images were reviewed and scored for anthropogenic scarring by recording the presence of visible scars resulting from fishing gear entanglement and vessel collisions in 21 defined body regions. In total, 20.0% (n = 30) of whales identified during the study period had detectable anthropogenic scarring, with 18.7% (n = 28) determined to have been previously entangled in fishing gear at least once and 2.0% (n = 3) to have survived at least one vessel collision. These estimates are likely to be conservative given the nature of the photo-identification data set, but indicate that male and female western gray whales are subject to anthropogenic interactions. Future studies designed to systematically estimate the frequency and rates of anthropogenic events are needed and would have direct conservation and management implications.